2004
DOI: 10.1111/j.1572-0241.2004.30272.x
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian Registry on Nonvariceal Upper Gastrointestinal Bleeding and Endoscopy (RUGBE): Endoscopic Hemostasis and Proton Pump Inhibition are Associated with Improved Outcomes in a Real-Life Setting

Abstract: These results appear to confirm the protective role of endoscopic therapy in patients with high-risk stigmata, and suggest that acute use of PPIs may be associated with a reduction of rebleeding in all patients, and lower mortality in patients with high-risk stigmata. Independent prospective validation of these observational findings is now required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
248
5
15

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(295 citation statements)
references
References 40 publications
20
248
5
15
Order By: Relevance
“…The number of comorbidities was significantly higher in patients who died and it was an independent predictor of death (OR: 1.6; 95% CI: 1-2.5, p = 0.045). This finding is similar to that observed in other studies, particularly RUGBE and PNED studies (3,5,8). On the other hand, hypovolemic shock as cause of death was significantly higher in patients without comorbidities than in those with comorbidities (48 vs. 21%, p = 0.02).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The number of comorbidities was significantly higher in patients who died and it was an independent predictor of death (OR: 1.6; 95% CI: 1-2.5, p = 0.045). This finding is similar to that observed in other studies, particularly RUGBE and PNED studies (3,5,8). On the other hand, hypovolemic shock as cause of death was significantly higher in patients without comorbidities than in those with comorbidities (48 vs. 21%, p = 0.02).…”
Section: Discussionsupporting
confidence: 80%
“…Recent prospective studies have identified different predictors of mortality; it is worth noting that the use of proton pump inhibitors (PPIs) significantly reduces mortality in patients both with and without high risk stigmata of rebleeding. Moreover, the use of endoscopic treatment has been demonstrated to reduce mortality in greater proportion than drug treatment (3)(4)(5)(6). However, it has been shown that the risk factors, complications and mortality rates described in controlled trials are lower than those reported in patients who received their attention on "day-today conditions" in a tertiary care community hospital (7), which illustrates more accurately the actual conditions of medical care.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Of note, external studies have found that red blood hematemesis is a high-risk feature for negative outcomes. 11 The GBS offers a high sensitivity with narrow confidence intervals, making this a useful tool to rule out high-risk UGIB.…”
Section: Commentarymentioning
confidence: 99%
“…Recent clinical studies demonstrate that the outcome of these patients can be improved when clinical resources are improved, decreasing the recurrence of bleeding (2,13,15,19) , the need for transfusion (13,19) and surgery (13) and reducing the length of stay and hospital costs (13,19) . A simple measure to enhance the outcome of NVUGIB patients could be the improvement of the timing when resuming a regular diet.…”
Section: Introductionmentioning
confidence: 99%